Significant Negative Relationship Between Running Habit and Academic Stress in Final-Year Students of UNNES - ARJUNAFA ALFINOOR; Roas Irsyada (Universitas Negeri Semarang, 2026)
Final-year students face peak academic pressure in the form of thesis writing, which can potentially cause academic stress. Physical activities such as running have emerged as a popular coping strategy; however, the quantitative relationship between natural running habits and academic stress among final-year students has not been extensively studied. This study aimed to analyze the relationship between running habits and academic stress among final-year students of Universitas Negeri Semarang (UNNES). A quantitative approach with a correlational design was employed. A sample of 130 final-year UNNES students from the class of 2022 who were working on their theses was selected using purposive sampling. Running habits were measured using an adaptation of the Godin Leisure-Time Exercise Questionnaire (GLTEQ), converted to MET per week. Academic stress was measured using an adaptation of the Educational Stress Scale for Adolescents (ESSA) with a 4-point Likert scale. Data were analyzed using Spearman's correlation test. The results showed that students' running habits were very low (mean MET per week = 74.43) and the average academic stress score was in the moderate category (mean = 36.91 out of 64). Spearman's correlation test revealed a significant negative relationship between running habits and academic stress (r_s = -0.246; p = 0.005), with a contribution of only 6.1%. In conclusion, there is a significant but weak negative relationship between running habits and academic stress. Running is beneficial as a stress management strategy but is not a single determining factor.